2022
DOI: 10.3390/sym14122537
|View full text |Cite
|
Sign up to set email alerts
|

Intuitionistic Fuzzy Rough Aczel-Alsina Average Aggregation Operators and Their Applications in Medical Diagnoses

Abstract: Managing ambiguous and asymmetric types of information is a very challenging task under the consideration of classical data. Furthermore, Aczel-Alsina aggregation operators are the new developments in fuzzy sets theory. However, when decision-makers need to use these structures in fuzzy rough structures, these operators fail to deal with such types of values, as fuzzy rough structures use lower and upper approximation spaces. Thus, an encasement of an intuitionistic fuzzy set has a chance of data loss, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In this section, we applied several existing AOs to the information provided by the decisionmakers in Tables 5-8 to evaluate the validity and feasibility of our proposed methodologies. We compared our approach with IFWA [19], IFWG [18], IvIFAAWA [31], IvIFAAWG [45], HFAAW [25], IFDWA [46], FDWG [46], IFRAAWA [24], IFRAAOW [24], IFRAAHA [24], IHFPWA [14], and IHFPG [14] methods. The results of existing AOs operators are shown in Table 12.…”
Section: The Effect Of the Conditional Probabilities In This Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we applied several existing AOs to the information provided by the decisionmakers in Tables 5-8 to evaluate the validity and feasibility of our proposed methodologies. We compared our approach with IFWA [19], IFWG [18], IvIFAAWA [31], IvIFAAWG [45], HFAAW [25], IFDWA [46], FDWG [46], IFRAAWA [24], IFRAAOW [24], IFRAAHA [24], IHFPWA [14], and IHFPG [14] methods. The results of existing AOs operators are shown in Table 12.…”
Section: The Effect Of the Conditional Probabilities In This Methodsmentioning
confidence: 99%
“…Additionally, we observed that IFWA [19], IFWG [18], HFAAW [25], IFDWA [46], IFDWG [46], IFRAAWA [24], IFRAAOW [24], and IFRAAHA [24] effectively handle intuitionistic fuzzy and hesitant fuzzy data. However, there are certain situations where these approaches may not be suitable.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…We aim to assess the preferences of our proposed approach in comparison to existing methods. The information system described in Table 1 serves as the basis for this comparative analysis, which includes the approaches referenced in [15,18,[45][46][47][48][49][50].…”
Section: Comparative Analysismentioning
confidence: 99%
“…Several researchers studied the prominence of operators related to the IF environment in [5][6][7][8][9][10] and presented many operators with this domain for different challenges. Ahmmad et al [11] introduced the Intuitionistic Fuzzy Rough Aczel-Alsina Aggregation Operators. Rahman et al [12][13][14][15] studied various methods in the PyF environment, such as PFWG operator, PFOWG operator, PFHG operator, PFWA operator, PFOWA operator, and PFHA operator.…”
Section: Introductionmentioning
confidence: 99%